Topcon cell encapsulation water-blocking adhesive film and topcon cell module with the same
Patent Information
- Application Number
- CN202210504565.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-05-10
AI Technical Summary
在TOPCon电池组件的使用过程中,可能会有部分水汽从电池组件背面进入电池组件内部,从而对电池片产生影响
1.本申请的双层结构阻水胶膜,包括疏水结构和亲水结构,疏水结构贴合电池片,有效阻止水汽的侵入,亲水结构远离电池片,对侵入电池组件内部的水汽产生吸附作用,两层膜之间相互配合,通过“疏水-亲水”结构,提高了胶膜的阻水效果;
Smart Images

Figure BDA0003636942780000061 
Figure BDA0003636942780000062 
Figure BDA0003636942780000071
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic cell encapsulation films, and more specifically, it relates to a TOPCon cell encapsulation water-blocking film and a TOPCon cell module with the film. Background Technology
[0002] Tunneling oxide passivated contact solar cells, or TOPCon cells for short, are a novel type of passivated contact solar cell first proposed by the Fraunhofer Institute for Solar Energy Research in Germany in 2013. TOPCon cells are N-type silicon substrate cells. First, an ultrathin layer of silicon oxide is prepared on the back of the cell, followed by the deposition of a doped silicon thin layer. These two layers together form the passivated contact structure, effectively reducing surface recombination and metal-to-metal recombination, providing greater potential for further improvement in the conversion efficiency of N-PERT cells. TOPCon cells retain and utilize existing P-type cell equipment processes to the greatest extent possible, requiring only the addition of boron diffusion and thin-film deposition equipment. They eliminate the need for back-side openings and alignment, greatly simplifying the cell manufacturing process and reducing the difficulty of mass production.
[0003] Currently, one type of single-glass TOPCon solar module exists, which is composed of tempered glass, encapsulation material, solar cells, encapsulation material again, and a backsheet, arranged from top to bottom. During the use of TOPCon solar modules, some moisture may enter the module from the back, affecting the solar cells. Therefore, the water-blocking performance of the module needs improvement. Summary of the Invention
[0004] In order to improve the waterproof and water-blocking performance of TOPCon battery modules and effectively slow down the aging of battery modules, this application provides a TOPCon battery encapsulation water-blocking film and a TOPCon battery module with the film.
[0005] In a first aspect, this application provides a TOPCon battery encapsulation water-blocking adhesive film, which adopts the following technical solution: a TOPCon battery encapsulation water-blocking adhesive film, starting from the side close to the battery cell, sequentially includes a first hydrophobic layer and a hydrophilic layer; The first hydrophobic layer is an EVA layer containing a hydrophobic compound; The hydrophilic layer is an EVA layer containing superabsorbent resin.
[0006] By adopting the above technical solution, a hydrophobic structure is set on the side closest to the battery cell, which effectively prevents the intrusion of water vapor and improves the water-blocking effect of the film, thereby effectively protecting the battery cell. Furthermore, a hydrophilic structure is also provided on the side of the hydrophobic structure away from the battery cell. This hydrophilic structure adsorbs water vapor that has penetrated into the battery module, effectively reducing the contact between water vapor and the battery cell. Thus, the water-blocking effect of the film is improved through a two-layer structure of one hydrophobic and one hydrophilic layer. Further, in the technical solution of this application, EVA is hydrophobically modified with a hydrophobic compound to form a hydrophobic structure, while the hydrophilic structure is formed by doping EVA with a superabsorbent resin.
[0007] Preferably, the total thickness of the TOPCon battery encapsulation water-blocking film is 300–1000 μm; The thickness ratio of the first hydrophobic layer to the hydrophilic layer is 1:(0.5~1.2).
[0008] By adopting the above technical solution, within the aforementioned range, the thickness of the water-blocking film is moderate, exhibiting good water-blocking effect and aging resistance, thus meeting the application requirements in this field. Furthermore, when the thickness ratio of the two layers of the water-blocking film is within the aforementioned range, the resulting water-blocking film exhibits superior water-blocking performance and aging resistance.
[0009] Preferably, it further includes a second hydrophobic layer disposed on the side of the hydrophilic layer away from the battery cell; The second hydrophobic layer is an EVA layer containing a hydrophobic compound.
[0010] By setting a second hydrophobic layer, the film forms a three-layer composite water-blocking structure of "hydrophobic-hydrophilic-hydrophobic", which further improves the water-blocking effect of the film, further reduces the impact of water vapor on the battery cells, and thus slows down the aging of the battery module.
[0011] Preferably, the total thickness of the TOPCon battery encapsulation water-blocking film is 300–1000 μm; The thickness ratio of the first hydrophobic layer, the hydrophilic layer, and the second hydrophobic layer is 1:(0.5~2):1.
[0012] By adopting the above technical solution, the total thickness of the water-blocking film is moderate, and its water-blocking effect and aging resistance are good, which can meet the application requirements in this field. Furthermore, when the thickness ratio of the three-layer structure of the water-blocking film is within the above range, the final water-blocking film exhibits superior water-blocking performance and aging resistance.
[0013] Preferably, the hydrophobic compound includes an organosilicon compound and / or a terpolymer.
[0014] In the technical solution of this application, the organosilicon compound can be a small molecule silane or a large molecule silane or a mixture of the two, wherein a silane with an organic group having 4 or more carbon atoms is preferred; the first monomer in the terpolymer can be ethylene, the second monomer can be maleic anhydride or glycidyl methacrylate, and the third monomer can be acrylic acid or methacrylic acid or a monomer of C1-C6 alkyl esters of acrylic acid and methacrylic acid.
[0015] Preferably, the content of the hydrophobic compound in the EVA layer containing the hydrophobic compound is 0.01 to 20 wt%.
[0016] By selecting the appropriate mass content of hydrophobic compounds, the EVA layer can achieve both excellent hydrophobicity and good adhesion.
[0017] In the technical solution of this application, the EVA layer containing hydrophobic compounds further includes 0.01-5 wt% of crosslinking agent, 0.01-5 wt% of co-crosslinking agent, 0-5 wt% of silane coupling agent, and 0-5 wt% of anti-aging agent.
[0018] The crosslinking agent can be one or more of the following: tert-butyl peroxycarbonate, 1,3-1,4-di(tert-butylperoxyisopropyl)benzene, benzoyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butyl peroxycarbonate, 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxycarbonate-2-ethylhexyl, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-pentyl peroxycarbonate, and tert-butyl peroxy3,3,5-trimethylhexanoate.
[0019] The crosslinking agent can be one or more of glycidyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxyglycerol triacrylate, ethyl carboxylate, isobornyl acrylate, isobornyl methacrylate, 2-hydroxyethyl methacrylate phosphate, and tripropylene glycol diacrylate.
[0020] The silane coupling agent can be one or more of vinyltrimethoxysilane, vinyltri(b-methoxyethoxy)silane, vinyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and vinyltriisopropoxysilane.
[0021] Anti-aging agents can be one or more of the following: hindered phenols, phosphites, p-benzophenones, benzotriazoles, hindered amine derivatives, o-hydroxybenzophenones, salicylates, and triazines.
[0022] Preferably, the first hydrophobic layer further contains 0.05 to 3 wt% of anti-corrosion filler.
[0023] By adopting the above technical solution, the aging resistance of the water-blocking film has been further improved.
[0024] Preferably, the superabsorbent resin includes polyacrylate resin.
[0025] Preferably, the content of superabsorbent resin in the hydrophilic layer is 0.1 to 3 wt%.
[0026] In the technical solution of this application, the polyacrylate resin can be sodium salt, zinc salt, ammonium salt, lithium salt, or calcium salt, and the molecular weight of the polyacrylate resin can be arbitrarily selected in the range of 8,000 to 50,000, therefore it is not intended to limit this application.
[0027] In the technical solution of this application, the hydrophilic layer further includes 0.01-5 wt% of a crosslinking agent, 0.01-5 wt% of a co-crosslinking agent, 0-5 wt% of a silane coupling agent, and 0-5 wt% of an anti-aging agent.
[0028] The use of crosslinking agents, co-crosslinking agents, silane coupling agents, and anti-aging agents in the hydrophilic layer can be the same as or different from that in the EVA layer containing hydrophobic compounds.
[0029] Secondly, this application provides a TOPCon battery module, which adopts the following technical solution: A TOPCon battery module includes a backplate, a first encapsulation material, battery cells, a second encapsulation material, and a glass panel stacked sequentially. The first encapsulation material is the TOPCon battery encapsulation water-blocking adhesive film provided in this application.
[0030] In summary, this application has at least the following beneficial effects: 1. The double-layer water-blocking film of this application includes a hydrophobic structure and a hydrophilic structure. The hydrophobic structure is attached to the battery cell and effectively prevents water vapor from entering. The hydrophilic structure is away from the battery cell and adsorbs water vapor that has entered the battery module. The two layers cooperate with each other and improve the water-blocking effect of the film through the "hydrophobic-hydrophilic" structure. 2. The three-layer water-blocking film of this application forms a "hydrophobic-hydrophilic-hydrophobic" water-blocking structure on the surface of the battery cell, which significantly improves the water-blocking effect of the film, effectively reduces the impact of water vapor on the battery cell, and slows down the aging of the battery module. 3. By optimizing the total thickness of the water-blocking film and the thickness ratio of each layer, this application enables the water-blocking film to meet the application requirements in this field and to have good water-blocking effect and aging resistance. Attached Figure Description
[0031] Figure 1 (a) The appearance of the DH film in Example 1 before aging; Figure 1 (b) The appearance of the film after DH aging for 500 hours in Example 1; Figure 1 (c) The appearance of the film after DH aging in Example 1 for 1000 hours; Figure 2 (a) shows the appearance of the DH film in Comparative Example 1 before aging; Figure 2 (b) The appearance of the film in Comparative Example 1 after DH aging for 500 hours; Figure 2 (c) shows the appearance of the film in Comparative Example 1 after DH aging for 1000 hours; Figure 3 (a) shows the appearance of the DH film in Comparative Example 2 before aging; Figure 3 (b) is the appearance of the film in Comparative Example 2 after DH aging for 500 hours; Figure 3 (c) shows the appearance of the film in Comparative Example 2 after DH aging for 1000 hours; Figure 4 The appearance of the battery pack DH after 1000 hours of aging in Example 1; Figure 5 The appearance of the battery pack DH in Comparative Example 1 after 1000 hours of aging; Figure 6 The image shows the appearance of the battery pack DH after 1000 hours of aging in Comparative Example 2. Detailed Implementation
[0032] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0033] Unless otherwise specified below, all raw materials used in the embodiments of this application are commercially available: The ethylene-vinyl acetate copolymer was sourced from Sirbon Petrochemical, model V2825.
[0034] Performance testing Single-glass TOPCon solar cell modules were prepared using the water-blocking films obtained in the following examples and comparative examples. From bottom to top, the modules consist of a backsheet, the water-blocking films obtained in the examples and comparative examples, solar cells, a conventional EPE film, and a glass panel. The resulting single-glass TOPCon solar cell modules were subjected to the following aging tests.
[0035] DH Test: Following the high temperature and humidity aging performance test method 5.5.11 in GB / T 29848-2018, the aging resistance of the water-blocking films in the examples and comparative examples was tested under constant temperature and humidity conditions. Test conditions: temperature 85℃±2℃, humidity 85%±5%; test time: 1000h. Power attenuation (%) was used as the DH test result. A smaller power attenuation indicates better aging resistance and better water-blocking effect of the water-blocking film.
[0036] PID Test: Following the high-temperature and high-humidity aging performance test method (5.5.11) in GB / T 29848-2018, the aging resistance of the water-blocking films in the examples and comparative examples was tested under constant temperature and humidity conditions. Test conditions: temperature 85℃±2℃, humidity 85%±5%, bias voltage 1500V; test time: 192h. Power attenuation (%) was used as the PID test result. A smaller power attenuation indicates better aging resistance and better water-blocking effect of the water-blocking film. Example
[0037] Example 1 A water-blocking adhesive film for TOPCon battery encapsulation consists of two layers, namely a first hydrophobic layer and a hydrophilic layer, starting from the side closest to the battery cell. The total thickness of the water-blocking adhesive film is 300 μm, and the thickness ratio of the first hydrophobic layer to the hydrophilic layer is 1:0.5.
[0038] The first hydrophobic layer is an EVA layer containing a hydrophobic compound. By weight percentage, the raw materials used to prepare the first hydrophobic layer consist of 98.75 wt% ethylene-vinyl acetate copolymer, 1 wt% hydrophobic compound octyltriethoxysilane, 0.1 wt% crosslinking agent tert-butyl peroxycarbonate isopropyl ester, 0.05 wt% co-crosslinking agent methyl methacrylate, 0.05 wt% silane coupling agent vinyltrimethoxysilane, and 0.05 wt% antioxidant 1010.
[0039] The hydrophilic layer is an EVA layer containing superabsorbent resin. By weight percentage, the raw materials used to prepare the hydrophilic layer consist of 98.75% ethylene-vinyl acetate copolymer, 1% sodium polyacrylate superabsorbent resin, 0.1 wt% crosslinking agent 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 0.05 wt% co-crosslinking agent ethyl carboxyacrylate, 0.05 wt% silane coupling agent vinyltriethoxysilane, and 0.05 wt% antioxidant 1010. The molecular weight of the sodium polyacrylate is 20,000–40,000.
[0040] The TOPCon battery encapsulation water-blocking adhesive film in this embodiment is prepared by the following method: The ethylene-vinyl acetate copolymer in the first hydrophobic layer raw material is extruded and granulated with a hydrophobic compound, and then blended with other additives to obtain the first hydrophobic layer mixed raw material. The ethylene-vinyl acetate copolymer, sodium polyacrylate superabsorbent resin and other additives in the hydrophilic layer raw material are blended to obtain the hydrophilic layer mixed raw material. The water-blocking film is obtained by co-extruding the raw materials of the first hydrophobic layer and the raw materials of the hydrophilic layer.
[0041] Furthermore, in other embodiments, when preparing the first hydrophobic layer mixed raw material, the ethylene-vinyl acetate copolymer, hydrophobic compound, and other additives can be directly blended to obtain the mixed raw material; alternatively, a portion of the ethylene-vinyl acetate copolymer and hydrophobic compound can be extruded and granulated, and then the resulting masterbatch can be blended with the remaining ethylene-vinyl acetate copolymer and additives to obtain the mixed raw material. Therefore, the above preparation methods should not be considered as limiting the technical solutions and specific embodiments of this application.
[0042] In other embodiments, the crosslinking agent in the raw materials of the first hydrophobic layer and the hydrophilic layer may also be tert-butyl peroxyisopropyl carbonate, 1,3-1,4-di(tert-butylperoxyisopropyl)benzene, benzoyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butyl peroxyisopropyl carbonate, 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxyisopropyl carbonate, etc. Butyl peroxycarbonate-2-ethylhexyl ester, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-pentyl peroxycarbonate, and 3,3,5-trimethyl peroxycarbonate The crosslinking agent may be one or more of the following: tert-butyl methyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxyglycerol triacrylate, carboxyethyl 2-acrylate, isobornyl acrylate, isobornyl methacrylate, 2-hydroxyethyl methacrylate phosphate, and tripropylene glycol acrylate; the silane coupling agent may be one or more of the following: vinyltrimethoxysilane, vinyltris(b-methoxyethoxy)silane, vinyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and vinyltriisopropoxysilane; the anti-aging agent may be one or more of the following: hindered phenols, phosphites, p-benzophenones, benzotriazoles, hindered amine derivatives, o-hydroxybenzophenones, salicylates, and triazines. The above selections are not intended to limit the technical solution and specific embodiments of this application.
[0043] Examples 2-5 A TOPCon battery encapsulation water-blocking film consists of two layers, starting from the side closest to the battery cell, consisting of a first hydrophobic layer and a hydrophilic layer.
[0044] The difference between Examples 2-5 and Example 1 is that the total thickness of the water-blocking adhesive film is different, as shown in the table below.
[0045] The performance of the water-blocking films obtained in Examples 1-5 was tested, and the results are shown in the table below.
[0046] The difference between Examples 1-5 lies in the total thickness of the water-blocking film. As shown in the table above, the water-blocking films obtained in Examples 1-5, when applied to TOPCon battery modules, exhibited power attenuation of less than 4% after the DH test and less than 3% after the PID test. However, the power attenuation of the water-blocking films obtained in Examples 2-5 was lower than that of the water-blocking film in Example 1. This may be because the water-blocking film in Example 1 was thinner, thus affecting its anti-aging performance and water-blocking effect. Furthermore, while the water-blocking film in Example 5 had a thickness of 1000 μm, its performance, although slightly better than Examples 2-4, was not significantly improved. Considering the thickness issue, Examples 3-4 are considered the superior examples among these five groups of examples.
[0047] Examples 6-7 A TOPCon battery encapsulation water-blocking film consists of two layers, starting from the side closest to the battery cell, consisting of a first hydrophobic layer and a hydrophilic layer.
[0048] The difference between Examples 6-7 and Example 3 is that the thickness ratio of the first hydrophobic layer to the hydrophilic layer is different, as shown in the table below.
[0049] The performance of the water-blocking films obtained in Examples 6-7 was tested, and the results are shown in the table below.
[0050] The difference between Examples 6-7 and Example 3 lies in the thickness ratio of the first hydrophobic layer to the hydrophilic layer. As shown in the table above, the water-blocking films obtained in Examples 6-7, when applied to TOPCon battery modules, exhibited power attenuation of less than 4% after the DH test and less than 3% after the PID test. Further analysis reveals that the water-blocking film obtained in Example 6 showed a power attenuation of only 3.0% after the DH test and only 2.1% after the PID test, both significantly lower than that of Example 3. This indicates that the anti-aging performance and water-blocking effect of the film in Example 6 are superior to those in Example 3. Furthermore, the water-blocking film obtained in Example 7 exhibits a higher power attenuation than that in Example 3. Therefore, Example 6 is the preferred embodiment.
[0051] Example 8 A water-blocking adhesive film for TOPCon battery encapsulation consists of three layers, namely a first hydrophobic layer, a hydrophilic layer, and a second hydrophobic layer, starting from the side closest to the battery cell. The total thickness of the water-blocking adhesive film is 300 μm, and the thickness ratio of the first hydrophobic layer, the hydrophilic layer, and the second hydrophobic layer is 1:0.5:1.
[0052] The raw materials used to prepare the first hydrophobic layer consist of 94.75 wt% ethylene-vinyl acetate copolymer, 5 wt% hydrophobic compound ethylene-glycidyl methacrylate-acrylic acid terpolymer, 0.1 wt% crosslinking agent tert-butyl peroxycarbonate, 0.05 wt% co-crosslinking agent methyl methacrylate, 0.05 wt% silane coupling agent vinyltrimethoxysilane, and 0.05 wt% antioxidant 1010.
[0053] The raw materials used to prepare the hydrophilic layer consist of 98.75% ethylene-vinyl acetate copolymer, 1% sodium polyacrylate superabsorbent resin (molecular weight 20,000-40,000), 0.1 wt% crosslinking agent 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 0.05 wt% co-crosslinking agent ethyl carboxylate 2-acrylate, 0.05 wt% silane coupling agent vinyltriethoxysilane, and 0.05 wt% antioxidant 1010.
[0054] The raw materials used to prepare the second hydrophobic layer are the same as those used for the first hydrophobic layer.
[0055] The TOPCon battery encapsulation water-blocking adhesive film in this embodiment is prepared by the following method: The ethylene-vinyl acetate copolymer and the ethylene-glycidyl methacrylate-acrylic acid terpolymer in the first hydrophobic layer raw material are extruded and granulated, and then blended with other additives to obtain the first hydrophobic layer mixed raw material. The ethylene-vinyl acetate copolymer, sodium polyacrylate superabsorbent resin and other additives in the hydrophilic layer raw material are blended to obtain the hydrophilic layer mixed raw material. The ethylene-vinyl acetate copolymer and ethylene-glycidyl methacrylate-acrylic acid terpolymer in the second hydrophobic layer raw material are extruded and granulated, and then blended with other additives to obtain the second hydrophobic layer mixed raw material. The water-blocking film is obtained by co-extruding the raw materials of the first hydrophobic layer, the raw materials of the hydrophilic layer, and the raw materials of the second hydrophobic layer.
[0056] Examples 9-12 A TOPCon battery encapsulation water-blocking film consists of a three-layer structure, starting from the side closest to the battery cell, consisting of a first hydrophobic layer, a hydrophilic layer, and a second hydrophobic layer.
[0057] The difference between Examples 9-10 and Example 8 is that the total thickness of the water-blocking film is different. The difference between Examples 11-12 and Example 9 is that the thickness ratios of the first hydrophobic layer, the hydrophilic layer, and the second hydrophobic layer are different, as shown in the table below.
[0058] The performance of the water-blocking films obtained in Examples 8-12 was tested, and the results are shown in the table below.
[0059] In Examples 8-12, the water-blocking films all have a three-layer structure, which is significantly different from the two-layer structure in Examples 1-7. Based on the data in the table above and the test results of Examples 1-7, it can be seen that the three-layer structure film has relatively better anti-aging performance and water-blocking effect. The difference between Examples 8, 9, and 10 lies in the total thickness of the water-blocking film. As shown in the table above, within the range of 300–1000 μm, the water-blocking effect and anti-aging performance of the water-blocking film increase with the increase of the total film thickness. The difference between Examples 9, 11, and 12 lies in the thickness ratio of the three-layer film structure. As shown in the table above, all three examples have good water-blocking effect and anti-aging performance, but Example 11 is relatively superior.
[0060] Example 13 A TOPCon battery encapsulation water-blocking film consists of a three-layer structure, starting from the side closest to the battery cell, consisting of a first hydrophobic layer, a hydrophilic layer, and a second hydrophobic layer.
[0061] The difference between this embodiment and Embodiment 8 is that, by weight percentage, the raw materials used to prepare the first hydrophobic layer consist of 93.75 wt% ethylene-vinyl acetate copolymer, 1 wt% hydrophobic compound octyltriethoxysilane, 5 wt% hydrophobic compound ethylene-glycidyl methacrylate-acrylate terpolymer, 0.1 wt% crosslinking agent tert-butyl peroxycarbonate, 0.05 wt% co-crosslinking agent methyl methacrylate, 0.05 wt% silane coupling agent vinyltrimethoxysilane, and 0.05 wt% antioxidant 1010.
[0062] In implementing the technical solution of this application, the inventors discovered that the first monomer in the terpolymer can be ethylene, the second monomer can be maleic anhydride or glycidyl methacrylate, and the third monomer can be acrylic acid, methacrylic acid, or a C1-C6 alkyl ester of acrylic acid and methacrylic acid. Using any one or more of the above-mentioned terpolymers as hydrophobic compounds results in similar final performance of the water-blocking film. Therefore, this application only uses one of them as an example for brief description, namely, the ethylene-glycidyl methacrylate-acrylic acid terpolymer.
[0063] Furthermore, the raw materials for preparing the second hydrophobic layer are the same as those for the first hydrophobic layer; the raw materials for preparing the hydrophilic layer, the preparation method of the water-blocking film, the total thickness of the water-blocking film, and the thickness ratio of the three-layer film structure are all the same as in Example 9.
[0064] The performance of the water-blocking film obtained in Example 13 was tested, and the results are shown in the table below.
[0065] As shown in the table above, the water-blocking film obtained in Example 13 exhibits better anti-aging and water-blocking properties than that in Example 9. This demonstrates that using 1 wt% octyltriethoxysilane and 5 wt% ethylene-glycidyl methacrylate-acrylic acid terpolymer as a hydrophobic compound can significantly improve the anti-aging and water-blocking properties of the water-blocking film.
[0066] Example 14 A TOPCon battery encapsulation water-blocking film consists of a three-layer structure, starting from the side closest to the battery cell, consisting of a first hydrophobic layer, a hydrophilic layer, and a second hydrophobic layer.
[0067] The difference between this embodiment and Embodiment 13 is that, by weight percentage, the raw materials used to prepare the first hydrophobic layer consist of 93.7 wt% ethylene-vinyl acetate copolymer, 1 wt% hydrophobic compound octyltriethoxysilane, 5 wt% hydrophobic compound ethylene-glycidyl methacrylate-acrylate terpolymer, 0.1 wt% crosslinking agent tert-butyl peroxycarbonate, 0.05 wt% co-crosslinking agent methyl methacrylate, 0.05 wt% silane coupling agent vinyltrimethoxysilane, 0.05 wt% antioxidant 1010, and 0.05 wt% anti-corrosion filler Mg(OH)2.
[0068] The performance of the water-blocking film obtained in Example 14 was tested, and the results are shown in the table below.
[0069] As can be seen from the data in the table above, Example 14 has enhanced anti-aging properties compared to Example 13.
[0070] In addition to Examples 1-14 above, the inventors also provided examples regarding the mass content of hydrophobic compounds in EVA layers containing hydrophobic compounds, the mass content of anti-corrosion fillers, and the mass content of superabsorbent resin in hydrophilic layers. However, the results show that the water-blocking effect of the water-blocking film increases with the increase of the mass content of hydrophobic compounds (within the range of 0.01 to 20 wt%); the corrosion resistance of the water-blocking film increases with the increase of the mass content of anti-corrosion fillers (within the range of 0.05 to 3 wt%); and the water-blocking effect of the water-blocking film increases with the increase of the mass content of superabsorbent resin (within the range of 0.1 to 3 wt%).
[0071] Comparative Example Comparative Example 1 A TOPCon battery encapsulation film is a common EPE three-layer co-extruded film, consisting of an EVA layer, a POE layer, and an EVA layer, starting from the side closest to the battery cell, with a total thickness of 300μm and a thickness ratio of 1:1:1 for each layer.
[0072] Comparative Example 2 A TOPCon battery encapsulation film is a single-layer EVA structure with a thickness of 300 μm. The raw materials used to prepare the film are the same as those used for the first hydrophobic layer in Example 1, calculated by weight percentage.
[0073] The performance of the water-blocking films obtained in Comparative Examples 1-2 was tested, and the results are shown in the table below.
[0074] As shown in the table above, the power attenuation of the encapsulating films obtained in Comparative Example 1 and Comparative Example 2 after the DH test was 4.2% and 4.9%, respectively; after the PID test, the power attenuation was 3.0% and 3.9%, respectively, both lower than the relevant values in Examples 1-14, especially Comparative Example 2, which showed the highest power attenuation. This indicates that the anti-aging performance and water resistance of the encapsulating films in Comparative Example 1 and Comparative Example 2 were significantly reduced compared to those in Examples 1-14.
[0075] Furthermore, during the DH test on the films obtained in Example 1, Comparative Example 1, and Comparative Example 2, the appearance of the battery modules was recorded before aging, after 500 hours of aging, and after 1000 hours of aging, as detailed below. Figure 1 , Figure 2 and Figure 3 As shown. By Figure 1 It can be seen that the water-blocking film in Example 1 showed no significant change in appearance after aging for 1000 hours, indicating that it has good aging resistance; Figure 2 It can be seen that the water-blocking film in Comparative Example 1 showed obvious black spots after aging for 1000 hours, indicating that its aging resistance was worse than that of Example 1; Figure 3 It can be seen that the water-blocking adhesive film in Comparative Example 2 turned black after aging for 1000 hours, indicating that its aging resistance is poor.
[0076] In addition, the films obtained in Example 1, Comparative Example 1, and Comparative Example 2, and the half-cell battery modules with 72 battery cells were subjected to DH tests, respectively. The appearance of the battery modules after the tests is as follows. Figure 4 , Figure 5 and Figure 6 As shown. By Figure 4 , Figure 5 and Figure 6 It can be seen that the aging resistance of Example 1 is relatively good, while the aging resistance of Comparative Example 1 and Comparative Example 2 is significantly poor.
[0077] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A water-blocking adhesive film for TOPCon battery encapsulation, characterized in that, Starting from the side closest to the solar cell, it consists of a first hydrophobic layer and a hydrophilic layer in sequence; The first hydrophobic layer is an EVA layer containing a hydrophobic compound; The hydrophilic layer is an EVA layer containing superabsorbent resin; It also includes a second hydrophobic layer disposed on the side of the hydrophilic layer away from the battery cell; The second hydrophobic layer is an EVA layer containing a hydrophobic compound; The total thickness of the TOPCon battery encapsulation water-blocking adhesive film is 300–1000 μm; The thickness ratio of the first hydrophobic layer, the hydrophilic layer, and the second hydrophobic layer is 1:(0.5~2):1; The hydrophobic compound includes organosilicon compounds and / or terpolymers, and the content of the hydrophobic compound in the EVA layer containing the hydrophobic compound is 0.01-20 wt%. The superabsorbent resin includes polyacrylate resin, and the content of superabsorbent resin in the hydrophilic layer is 0.1-3 wt%.
2. The TOPCon battery encapsulation water-blocking adhesive film according to claim 1, characterized in that, The first hydrophobic layer also contains 0.05 to 3 wt% of corrosion-resistant filler.
3. A TOPCon battery module, characterized in that, It includes a backplate, a first encapsulation material, a battery cell, a second encapsulation material, and a glass panel that are stacked sequentially. The first encapsulation material is the TOPCon battery encapsulation water-blocking adhesive film as described in any one of claims 1-2.
Citation Information
Patent Citations
Multilayer packaging glue film for solar cell and preparing technology thereof
CN105774154A
Packaging adhesive film and preparation method thereof
CN111334200A
Packaging structure and packaging method of solar cell
CN111370513A